UPROOTED AND RESETTLED. THE DRAMA OF VARIABLE BORDERS IN THE CONTEMPORARY POLISH THEATER - Dobrowolski, Piotr (Porównania, 2013)
The article describes the changes in discourse in recent Polish historical plays on the basis of texts about the Recovered Territories. The characters in the play are the people left on the margins of great history: the Germans deported from the territories of pre-war Germany that became part of Poland after World War II and the people from the East resettled by the authorities to this land. The theatre that transfers the experience of the uprooted and the resettled gives them the opportunity to speak with their own voice. The theatre breaks the „historical amnesia” of those who used to be excluded and voiceless. It opens a new, postcolonial perspective on Polish history. The discussed texts and plays are Paweł Demirski’s Niech żyje wojna! (Long live the war!), Transfer! by Jan Klata and Marcin Liber’s staging of Trash Story written by Magda Fertacz.